The Handbook of Salutogenesis - Mittelmark, Maurice B.; Bauer, Georg F.; Vaandrager, Lenneke; Pelikan, Jürgen M.; Sagy, Shifra; Eriksson, Monica; Lindström, Bengt; Meier Magistretti, Claudia (Springer Nature, 2022)
This open access book is a thorough update and expansion of the 2017 edition of The Handbook of Salutogenesis, responding to the rapidly growing salutogenesis research and application arena. Revised and updated from the first edition are background and historical chapters that trace the development of the salutogenic model of health and flesh out the central concepts, most notably generalized resistance resources and the sense of coherence that differentiate salutogenesis from pathogenesis. From there, experts describe a range of real-world applications within and outside health contexts. Many new chapters emphasize intervention research findings. Readers will find numerous practical examples of how to implement salutogenesis to enhance the health and well-being of families, infants and young children, adolescents, unemployed young people, pre-retirement adults, and older people. A dedicated section addresses how salutogenesis helps tackle vulnerability, with chapters on at-risk children, migrants, prisoners, emergency workers, and disaster-stricken communities. Wide-ranging coverage includes new topics beyond health, like intergroup conflict, politics and policy-making, and architecture. The book also focuses on applying salutogenesis in birth and neonatal care clinics, hospitals and primary care, schools and universities, workplaces, and towns and cities. A special section focuses on developments in salutogenesis methods and theory. With its comprehensive coverage, The Handbook of Salutogenesis, 2nd Edition, is the standard reference for researchers, practitioners, and health policy-makers who wish to have a thorough grounding in the topic. It is also written to support post-graduate education courses and self-study in public health, nursing, psychology, medicine, and social sciences.